If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x-8=-1x-4
We move all terms to the left:
-3x-8-(-1x-4)=0
We get rid of parentheses
-3x+1x+4-8=0
We add all the numbers together, and all the variables
-2x-4=0
We move all terms containing x to the left, all other terms to the right
-2x=4
x=4/-2
x=-2
| (4)=14-5x | | (2x)5=11 | | 2(7x-4)=38+6x-6 | | 117=-6y+3 | | 5y-59+8=180 | | 3(4m-5)=2(6m-1) | | 5y-59=8 | | x/2=19/8 | | 2n+3=90 | | d/5=-11 | | -2=-5r+3 | | 85-2x=94-3x | | 30(x-10)=180 | | 2(y-3)=7(6) | | 12^2x-2=24 | | -x(+13)=-2(x-2) | | 14.x=0 | | 9^(x)+3^(x+1)=28 | | 4k-4(9-4k)=5k+5k | | 8= -2n | | 5+6x=41+3x | | 2x+(-9+x)=12 | | 2x-7=7x-7 | | 8z=6z+2 | | x+11/10=109/15 | | 13=m-8 | | (7x-4)=(8x-27)° | | 1/3x+10=3/5x+0 | | x-7+34=40 | | 9r-7=180 | | x-7+34=4 | | 2w-8=1+w |